PELAKSANAAN KEWENANGAN DINAS KOMUNIKASI, INFORMATIKA, STATISTIK DAN PERSANDIAN KOTA PEKANBARU MENCEGAH PENYEBARAN HOAX MEDIA SOSIAL DI KOTA PEKANBARU TAHUN 2024 - Fahreza, Rizki; ,, Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to describe the implementation of the authority of the Pekanbaru City Communication and Information Service to prevent the spread of hoaxes in Pekanbaru City. This study aims to examine the implementation of the authority of the Pekanbaru City Communication and Information Service in monitoring and preventing hoax issues. Through an in-depth analysis of the strategies, efforts, and cooperation that have been carried out by the Communication and Information Service, this study is expected to provide a better understanding of the extent to which the institution is able to respond to the challenges of disinformation at the local level. This study is a descriptive study with a qualitative approach. The types of data are primary data and secondary data, primary data are obtained directly from informants. While secondary data is supporting data or strengthens primary data. Data collection techniques are carried out by interviews and documentation. There are 4 stages of data analysis techniques used, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that describing the implementation of the authority of the Pekanbaru City Communication and Information Service to prevent the spread of hoaxes in Pekanbaru City as a whole is not yet effective. This is because several aspects have not run properly. The results of this study are based on the theory put forward by Dadang Surjanto. shows that there are shortcomings in the implementation of authority that has not been effective as it should be in handling the spread of hoaxes in Pekanbaru City. Keywords: Authority, Hoax, Effective